2021
DOI: 10.1186/s40854-021-00251-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of gross domestic product on the financing and investment efficiency of China’s commercial banks

Abstract: China’s commercial banks have developed at a very rapid speed in recent decades. However, with global economic development slowing down, the impact of gross domestic product growth as an exogenous factor cannot be ignored. Most existing studies only consider the internal factors of banks, and neglect their external economic factors. This study thus adopts an undesirable dynamic slacks-based measure under an exogenous model in combination with the Kernel density curve to explore the efficiency of state-owned co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
7
0
2
Order By: Relevance
“…In the real sector, the disbursed financing will surely continue to increase the real output, and as the result it increases the economic performance (Ahmadvand, et al, 2021;Asnuri, 2013). Studies have revealed that financing activities have a significant effect on the economic performance (Nofrianto et al, 2021;Shi et al, 2021). Related to this connection, this study tries to test the hypothesis below.…”
Section: H5: Iimm Has a Significant Effect On Economic Performancementioning
confidence: 94%
“…In the real sector, the disbursed financing will surely continue to increase the real output, and as the result it increases the economic performance (Ahmadvand, et al, 2021;Asnuri, 2013). Studies have revealed that financing activities have a significant effect on the economic performance (Nofrianto et al, 2021;Shi et al, 2021). Related to this connection, this study tries to test the hypothesis below.…”
Section: H5: Iimm Has a Significant Effect On Economic Performancementioning
confidence: 94%
“…From the perspective of the subject of economic activities, efficiency is reflected by the performance of a single transaction subject [9]. Resource allocation efficiency refers to whether resources can be concentrated to the subject that can give full play to its efficiency.…”
Section: Financing Efficiencymentioning
confidence: 99%
“…Second, financial ecology soil, referring to the direct material basis of financial ecology, provides economic and policy support for financial ecology growth. A solid macro-economic foundation means adequate market capital supply, reducing the financing difficulty and improving financing efficiency [ 19 ]. Governments can provide direct fiscal subsidies by formulating the financial scheme [ 20 ].…”
Section: Theoretical Analysismentioning
confidence: 99%